Letter from Roger Casement to Francis H. Cowper about how he is returning home from the Congo and hopes to see him in Lisbon - Casement, Roger, 1864-1916; Cowper, Francis H. (1902)
Casement says he is leaving the bulldog ["John"] behind as he does not want his other dog, "Rags", to "die of grief and rage and envy".
Manuscript in black ink on embossed paper: "British Consulate, / Congo Independent State". Envelope addressed to: "F.H. Cowper Esq, / Consul d'Angle terre / Lisbon / Portugal".
Keywords: Casement, Roger, -- 1864-1916 -- Correspondence; Cowper, Francis H. -- Correspondence; Irish -- Africa -- 20th century; Diplomatic and consular service, British